Parents' perception of children's obesity, in Al-Qassim, Saudi Arabia - Abdulrahman A Al-Mohaimeed (Wolters Kluwer Medknow Publications, 2016)
Background and Objectives: Although the prevalence of childhood obesity has increased significantly in Saudi Arabia, parents are unable to appreciate obesity in their child. The objective of the study was to identify the percentage of parents who misclassify the status of child's weight, and determine whether there is a difference between those parents whose children are overweight and obese and those with children of normal weight. Materials and Methods: This cross-sectional study included 601 children aged 6-10 years. The children were recruited from the primary schools located in Al-Qassim, Saudi Arabia. The body mass index of the children was assessed in the school, and their parents responded to a self-administered questionnaire which contained questions on parental perception of the children's weight/obesity status. Data were entered and analyzed using SPSS. Results: Parents with overweight/obese children had significantly more misclassification than those with normal weight children. Ninety percent of parents of the 81 overweight children misclassified and reported that their child had normal weight, while 65% of parents of the 61 obese children, misclassified the child's weight status. Conclusions: The level of misclassification of children's weight status by parents is high. Saudi parents with overweight and obese children do not recognize their child's weight status. Parents' awareness of childhood obesity and its negative health impact needs to be improved.